Stochastic mortality, macroeconomic risks, and life insurer solvency - Katja Hanewald; Thomas Post; Helmut Gründl (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
Motivated by a recent demographic study establishing a link between macroeconomic fluctuations and the mortality index kt in the Lee-Carter model, we assess the impact of macroeconomic fluctuations on the solvency of a life insurance company. Liabilities in our stochastic simulation framework are driven by a GDP-linked variant of the Lee-Carter mortality model. Furthermore, interest rates and stock prices are allowed to react to changes in GDP, which itself is modeled as a stochastic process. Our results show that insolvency probabilities are significantly higher when the reaction of mortality rates to changes in GDP is incorporated.
Keywords: G22; G23; G28; G32; E32; J11; 330; Life insurance; asset-liability management; stochastic mortality; Lee-Carter model; business cycle; Lebensversicherung; Betriebliche Liquidität; Konkurs; Konjunktur; Sterblichkeit; Stochastischer Prozess; Theorie